(untitled) (Sirte Journal of Medical Sciences, 2022)
A simple, accurate, and cost-effective UV-spectrophotometric method for determining Paracetamol in tablet pharmaceutical formulations has been developed. The method was designed and validated in accordance with the criteria of the International Conference on Harmonization (ICH). The developed method was validated statistically concerning linearity range, precision, accuracy, the limit of detection and the limit of quantitation. The study used ethanol-water as a solvent, and λmax was found to be 243 nm. In the range of 2.0–16.0 µg mL-1, a pure drug concentration was prepared, and linear regression analysis revealed a good linear connection with an R2 value of 0.999. The detection and quantification limits were determined to be 0.5 and 1.5 µg mL-1, respectively. The recoveries ranged between 103 and 109%, and the relative standard deviation was less than 2%, indicating that this method was developed for the potential determination of Paracetamol in tablet dosage formulations.